2017
DOI: 10.3390/jcm6080080
|View full text |Cite
|
Sign up to set email alerts
|

Use of FGF-21 as a Biomarker of Mitochondrial Disease in Clinical Practice

Abstract: Recent work has suggested that fibroblast growth factor-21 (FGF-21) is a useful biomarker of mitochondrial disease (MD). We routinely measured FGF-21 levels on patients who were investigated at our centre for MD and evaluated its diagnostic performance based on detailed genetic and other laboratory findings. Patients’ FGF-21 results were assessed by the use of age-adjusted z-scores based on normalised FGF-21 values from a healthy population. One hundred and fifty five patients were investigated. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Similarly, here, fibroblast growth factor 21 (FGF21), an endocrine hormone that regulates energy homeostasis, also showed significant upregulation. FGF21 concentration in plasma is increased in patients with obesity, insulin resistance, and metabolic syndrome . Our finding coincided with the aforementioned literature that revealed that fructose can activate hepatic transcription factor ChREBP, resulting in stimulation of hepatic FGF21 expression .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, here, fibroblast growth factor 21 (FGF21), an endocrine hormone that regulates energy homeostasis, also showed significant upregulation. FGF21 concentration in plasma is increased in patients with obesity, insulin resistance, and metabolic syndrome . Our finding coincided with the aforementioned literature that revealed that fructose can activate hepatic transcription factor ChREBP, resulting in stimulation of hepatic FGF21 expression .…”
Section: Discussionsupporting
confidence: 91%
“…reported comparable correlation between FGF‐21 and GDF‐15 in the plasma of patients with mitochondrial diseases. Absence of age differences in FGF‐21 concentrations could be explained by a small number of samples within the control group, although other authors found age differences in comparable groups . We also did not find any associations between the evaluated cytokines and body mass index, lactate, creatine kinase, organic acids pattern in the urine (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…et al reported raised levels of FGF-21 in mitochondrial translation defects and mtDNA deletions and correlated positively with disease severity being a possible biomarker to follow up [74]. Morovat A. et al demonstrated that FGF-21 displays considerable overlapping values between mitochondrial and nonmitochondrial diseases, increased levels in other conditions yet stability in repeated measurements to follow up procedures and important positive correlation in ophthalmoplegia in adults even suggesting to dismiss muscle assessment to produce a definite diagnosis [75]. Given the disagreement, a Russian group recently published results comparing mitochondrial disease groups with nonmitochoindrial controls for each biomarker and had no significant results in their cohort studies pointing raised levels in metabolic nonmitochondrial group, though mitochondrial group had higher values, which require further investigation of these biomarkers [76].…”
Section: Biochemical Investigationmentioning
confidence: 99%